Satisfaction Levels of Students and Professors with the Integration Workshop on Human Morphophysiology III - Luis Alberto Mass Sosa; Galia Ibis Pérez Rumbaut; Georgina Jiménez Estrada; Ana Margarita López Rodríguez del Rey; Ada Sánchez Lozano; Sandra Cecilia Williams Serrano (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2012)
Background: Integration is a skill that is acquired and developed through exercises and learning activities designed for this purpose. Objective: To determine the level of satisfaction of students and professors with the integration workshop on the subject of Human Morphophysiology III in medicine studies from 2010 to 2011. Methods: A descriptive study was conducted at the Faculty of Medical Sciences of Cienfuegos, in the 2010-2011 academic years, with all students and professors who attended the workshop on the subject of Integration of Human Morphophysiology III, of medicine studies, (91 students and 16 teachers). A questionnaire was administered to students and professors who addressed the organizational and methodological considerations for the development of these activities. Results: Students were satisfied with the usefulness of the study guide (Iadov 0.68) and the activities for the consolidation of the contents (Iadov 0.60). Professors showed satisfaction with quality of the guide, usefulness of tasks and organization of the workshop (Iadov 0.81). Students reported the following as positive aspects of the workshop: basic clinical linking (36.46%), usefulness of the activity for the consolidation of content (32.97%) and the participation of professors in the clinical area (26.37 %). Coincidentally, professors also considered as positive the latter two aspects. There were contradictions with the participation of students and professors. Conclusions: There was satisfaction in student and professors with organizational aspects and methodological considerations taken into account.